2017
DOI: 10.3171/2016.12.peds16197
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of epilepsy surgery in 85 pediatric patients followed up for over 10 years: a retrospective survey

Abstract: OBJECTIVEThe aim of this study was to investigate the treatment outcomes and social engagement of patients who had undergone pediatric epilepsy surgery more than 10 years earlier.METHODSBetween 1983 and 2005, 110 patients younger than 16 years underwent epilepsy surgery at the National Epilepsy Center, Shizuoka Institute of Epilepsy and Neurological Disorders. The authors sent a questionnaire to 103 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 66 publications
9
39
1
5
Order By: Relevance
“…Ultimately, the surgical result arises from the accuracy of defining the region of seizure onset or disrupting a critical network essential for the propagation of the seizure. 9,12 Neocortical epilepsy predominates in children and is difficult to localize. 7,8,12 The neocortex has robust projections, which make rapid and diffuse spread of epileptiform discharges common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, the surgical result arises from the accuracy of defining the region of seizure onset or disrupting a critical network essential for the propagation of the seizure. 9,12 Neocortical epilepsy predominates in children and is difficult to localize. 7,8,12 The neocortex has robust projections, which make rapid and diffuse spread of epileptiform discharges common.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Neocortical epilepsy predominates in children and is difficult to localize. 7,8,12 The neocortex has robust projections, which make rapid and diffuse spread of epileptiform discharges common. The characteristic pathologic substrate is cortical dysplasia, which is often MRI occult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In appropriately selected patients, resection of this localized seizure origin can be curative. Despite the promise of this approach, surgical outcomes remain highly variable, even in optimal candidates (Cohen-Gadol et al, 2004;Cohen-Gadol et al, 2006;Hosoyama et al, 2017;Najm et al, 2013). Emerging studies motivated by these inconsistencies have demonstrated that pediatric focal epilepsy is not a localized disorder, but rather a disease of large-scale, distributed neural networks (Spencer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Оценка влияния операции на частоту приступов, по классификации J. Engel, продемонстрировала, что у 54,54% пациентов удалось добиться полного избавления от инвалидизирующих приступов в долгосрочной перспективе (от 3 до 7 лет). Эти данные совпадают с показателями благоприятных исходов, полученными другими исследователями [24,25].…”
unclassified